Characterization and regulated naproxen release of hydroxypropyl cyclosophoraose-pullulan microspheres - Choi, Jae Min; Lee, Benel; Jeong, Daham; Park, Kyeong Hui; Choi, Eun-Ji; Jeon, Yong-Joon; Dindulkar, Someshwar D.; Cho, Eunae; Do, Sun Hee; Lee, Kyungho; Lee, Im-Soon; Park, Seyeon; et al. (Journal of industrial and engineering chemistry (Seoul, Korea), 2017)
[Display omitted] •Hybrid microspheres of biocompatible polysaccharide pullulan (Pul) and hydroxypropyl cyclosophoraoses (HPCys) were prepared.•The HPCys-Pul microspheres showed both effective encapsulation and controlled release of naproxen (NPX).•Those microspheres were completely characterized by TGA, XRD, FE-SEM, FT-IR, and solid-state NMR spectroscopy.•Hybrid HPCys-Pul microspheres resulted in a pH-regulated release system as well as enhanced entrapment efficiency for NPX. Hydroxypropyl cyclosophoraose-pullulan (HPCys-Pul) microspheres were designed as a novel hybrid system of biocompatible pullulan matrice and pendant hydroxypropyl cyclosophoraoses with drug complexing ability. The HPCys-Pul microspheres were prepared by emulsion crosslinking method, and characterized using thermogravimetric analysis, Fourier transform infrared spectroscopy, scanning electron microscopy, and solid state NMR spectroscopy. By virtue of hydroxypropyl cyclosophoraoses, the developed microspheres can encapsulate 4.2-fold more naproxen than pullulan microspheres. Korsmeyer–Peppas model was introduced for describing release kinetics. In vivo naproxen release analysis was carried out in Sprague-Dawley (SD) rats. From those results HPCys-Pul microsphere will be a promising platform for controlled drug delivery.